On-farm assessment and demonstration of best management practices for direct-seeded rice in Timor-Leste - Goto, Yusaku; Egusa, Taisuke; Yamasaki, Yuji; Kumar, Virender; Sato, Takeshi; Kato, Yoichiro (Wiley, 2025)
Direct-seeded rice (Oryza sativa) cultivation (DSR) is gradually replacing transplanted rice cultivation (TPR) across tropical Asia owing to labor shortages. However, the yields in DSR are lower than those in TPR under current farmer practices (FPs). It would be useful to introduce best management practices (BMPs), holistic technology packages prepared by researchers and extension staff, to improve DSR yield. We aimed at quantifying the effect of BMPs application on the on-farm yield, input factors (labor requirements and production costs), and cost–benefit performance of DSR and comparing it with the results of TPR. On-farm trials were conducted for 2 years in Timor-Leste (East Timor) and categorized farmers into a 2 × 2 experimental design: farmers who used FPs in DSR, BMPs in DSR, FPs in TPR, or BMPs in TPR. There were no significant yield differences between DSR and TPR under BMPs (3.5 vs. 3.6 t ha−1), but DSR produced a 20% lower yield than TPR under FPs (2.4 vs. 3.0 t ha−1). Yield increases due to BMPs were greater in DSR (+46%) than in TPR (+20%). The benefit–cost ratio of BMPs in DSR was 21% higher than that of BMPs in TPR (1.48 vs. 1.22). DSR farmers can achieve yields similar to those of TPR farmers by applying BMPs, with less labor and lower production costs, even where subsistence farming prevails. The effects of BMPs on DSR and TPR in this study suggest that the BMPs could improve land and labor productivities through DSR in tropical agricultural development programs.